School Efforts to Manage Interpersonal Conflicts Among Students: A Case Study at SMA Negeri 1 Lembar, West Lombok - Mardhani, Baiq Yunita Ayu; Ismail, M.; Alqadri, Bagdawansyah; Haslan, Muhammad Mabrur (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to investigate the efforts and challenges faced by SMA Negeri 1 Lembar in addressing interpersonal conflicts among its students. A qualitative approach with a phenomenological perspective was employed, and data were collected through interviews, observations, and documentation. The results show that the school has implemented various efforts to address interpersonal conflicts, including school policies and programs. However, the school also faces challenges such as a lack of trained human resources and limited facilities. This study concludes that the school's efforts to address interpersonal conflicts involve developing policies and programs as a preventive measure. The study is expected to contribute to the development of strategies for handling interpersonal conflicts in schools and raise awareness about the importance of collaboration between schools, teachers, and parents in creating a conducive learning environment.